Proposta de uma metodologia econômica para o desenvolvimento de SIG 3D - Nero, Marcelo Antonio; Lapa, Rodrigo Amaral [UNESP]; Sato, Simone Sayuri (My University, 2012)
The development of a Geographic Information System (GIS) needs to import 3D solid elements created in three dimensions. The acquisition of these data is done, in most cases, by using a LIDAR (Light Detection and Ranging). Another possibility is the use of mobile mapping, integrated GNSS and inertial system (IMU). Subsequently, we conducted a thorough editing job. Certainly, if the scale of the project is larger, the amount of detail is greater and hence the cost and time of acquisition will be higher. Thus, the development of a GIS project for 3D applications, such as for the area of power distribution is still impractical for use in Brazil due to the high cost of 3D acquisition. Thus, to make the use of these tools in 3D GIS environment feasible an alternative methodology for cost reduction was developed. The alternative presented here was the use of an existing collection of photos, in this case refering to coverage on the scale 1:8000. Additionally, it used the 1:2000 base map and a high resolution image from the QuickBird satellite (used as a backdrop and applied as texture in digital terrain model). On developing the project, we used the Opensource software, complete VTP (Virtual Terrain Project), including the libraries OGR, GDAL and vtdata vtlib compatible with MFC (Microsoft Foundation Class), GDI + (Graphics Device Interface Plus), and the database PostgreSQL (free database). 3D data modeling was done in order to reduce costs for an application to electricity distribution. Finally, we performed an analysis of the relative positional quality, and obtained satisfactory quantitative results, as presented in the text below.
Proposal for an economical methodology for the development of 3D GIS
Keywords: 3D GIS; Economical methodology; Opensource; Photogrammetric restitution; Three dimensional acquisitions